Предмет: Математика,
автор: mariaexe
(2х-6)²(х-6)=(2х-6)(х-6)²
Ответы
Автор ответа:
0
(2х- 6)²(х- 6)=(2х- 6)(х- 6)²
(2х- 6)²(х- 6) - (2х- 6)(х- 6)² =0
(2х- 6)*(х- 6) *( (2х- 6) -(х- 6) ) = 0
(2х- 6)*(х- 6) *( 2х- 6 -х+6 ) = 0
(2х- 6)*(х- 6) * х= 0
(2х- 6)= 0 или (х- 6) =0 или х= 0
х₁=3 х₂=6 х₃=0
Похожие вопросы
Предмет: Русский язык,
автор: White2008
Предмет: Алгебра,
автор: wyhwjgdjej
Предмет: Геометрия,
автор: morex797
Предмет: Математика,
автор: яночка677
Предмет: Математика,
автор: мимимишка9